Issue voting in Portugal: The 2002 legislative elections - Freire, A. (West European Politics, 2004)
This article analyses the relative impact of position versus performance issues in Portuguese voting behaviour at the 2002 legislative elections and examines the relative importance of issues compared to other determinants of voting behaviour. The article first defines issues and then presents a model of voting choice, before examining the salience of different issues. The impact of issues, as opposed to other major voting determinants, is evaluated as vote predicting factor.